Cell-impedance-based label-free technology for the identification of new drugs. (3rd April 2017) - Lundstrom, Kenneth
ABSTRACT: Introduction : Drug discovery has progressed from relatively simple binding or activity screening assays to high-throughput screening of sophisticated compound libraries with emphasis on miniaturization and automation. The development of functional assays has enhanced the success rate in discovering novel drug molecules. Many technologies, originally based on radioactive labeling, have sequentially been replaced by methods based on fluorescence labeling. Recently, the focus has switched to label-free technologies in cell-based screening assays. Areas covered : Label-free, cell-impedance-based methods comprise of different technologies including surface plasmon resonance, mass spectrometry and biosensors applied for screening of anticancer drugs, G protein-coupled receptors, receptor tyrosine kinase and virus inhibitors, drug and nanoparticle cytotoxicity. Many of the developed methods have been used for high-throughput screening in cell lines. Cell viability and morphological damage prediction have been monitored in three-dimensional spheroid human HT-29 carcinoma cells and whole Schistosomula larvae. Expert opinion : Progress in label-free, cell-impedance-based technologies has facilitated drug screening and may enhance the discovery of potential novel drug molecules through, and improve target molecule identification in, alternative signal pathways. The variety of technologies to measure cellular responses through label-free cell-impedance based approaches all support future drug development and should provide excellent assets for finding better medicines.